How to predict financial stress? An assessment of Markov switching models - Thibaut Duprey; Benjamin Klaus (Bank of Canada, 2017)
This paper predicts phases of the financial cycle by using a continuous financial stress measure in a Markov switching framework. The debt service ratio and property market variables signal a transition to a high financial stress regime, while economic sentiment indicators provide signals for a transition to a tranquil state. Whereas the in-sample analysis suggests that these indicators can provide an early warning signal up to several quarters prior to the respective regime change, the out-of-sample findings indicate that most of this performance is owing to the data gathered during the global financial crisis. Comparing the prediction performance with a standard binary early warning model reveals that the Markov switching model is outperforming the vast majority of model specifications for a horizon up to three quarters prior to the onset of financial stress.
Keywords: C54; G01; G15; 330; Business fluctuations and cycles; Central bank research; Econometric and statistical methods; Financial markets; Financial stability; Financial system regulation and policies; Monetary and financial indicators